THE SUSTAINABILITY OF THE INFRASTRUCTURE SYSTEM AT UNIVERSITI MALAYSIA SABAH IN GENERATING A CONDUCIVE LEARNING ENVIRONMENT - Mohd Nur Hidayat Hasbollah Hajimin; Syamsul Azizul Marinsah; Irma Wani Othman; Mohd Sohaimi Esa2 (Journal of Islamic, Social, Economics and Development, 2021)
This paper discusses the visibility of infrastructure integration in the context of sustainability of a conducive learning environment for international students at UMS in the post Covid-19th millennium. The sustainability of a conducive learning environment process indicates the commitment of the university’s management in materialising the country’s internationalisation policy. The concept of conducive environmental sustainability is centred on the vital functions and effectiveness of the infrastructure system implemented by a university. It has continuity with a system of well-being and welfare support which is an attractive factor in the selection of Malaysia as a study destination for international students. Ideally, the provision of a university infrastructure includes three components, (a) learning and teaching infrastructure, (b) Information Technology (IT) infrastructure, and (c) research infrastructure. This study has two main objectives, namely (1) to explore the views of international students on the sustainability of the infrastructure system in UMS and (2) to evaluate the views of students on the responsibility of UMS in providing a conducive learning environment. A qualitative approach using in-depth interview techniques was selected based on the background of an exploratory study. A total of 13 international students studying at UMS were interviewed online to obtain empirical data which allows the application of thematic techniques to the transcription of such in-depth interviews through the process of coding dominant and subdominant themes. The discussion of this paper utilises a selection of narratives from study respondents that focuses on three dominant themes namely; (i) views of international students on the sustainability of UMS infrastructure and physical environment, (ii) views of international students on psychosocial environment towards generating a conducive teaching and learning environment in UMS, (iii) the views of international students on the efficiency of the service system of the Centre for Internationalisation and Global Engagement Universiti Malaysia Sabah (UMS).